Poria cocos polysaccharides rescue pyroptosis-driven gut vascular barrier disruption in order to alleviates non-alcoholic steatohepatitis. (5th October 2022) - Ye, Haixin; Ma, Shuoyi; Qiu, Zhantu; Huang, Sha; Deng, Guanghui; Li, Yunjia; Xu, Shu; Yang, Menghan; Shi, Hao; Wu, Chaofeng; Li, Min; Zhang, Jia; et al.
Abstract: Ethnopharmacological relevance: Poria cocos polysaccharides (PCP) are abundant in Poria cocos (Schw.) Wolf (Poria). This is a common traditional Chinese medicine used to treat gastrointestinal and liver diseases. Poria cocos dispel dampness and enhance gastrointestinal functions, strongly affecting the treatment of non-alcoholic fatty liver disease. Still, the mechanism is not yet clear. Aim of the study: The latest research found that protecting the integrity of the intestinal barrier can slow down the progression of non-alcoholic fatty liver disease (NAFLD). Hence, our research ought to explore the protective mechanism of PCP on the intestinal barrier under a high-fat diet and to clarify the relationship between intestinal barrier damage and steatohepatitis. Materials and methods: H&E staining was done to evaluate pathological damage, whereas Nile red and oil red O staining was conducted to evaluate hepatic fat infiltration. Immunofluorescence staining and immunohistochemical staining were used to detect protein expression and locations. Bone marrow-derived macrophages were isolated for in vitro experiments. ONOO- and ROS fluorescent probes and MDA, SOD, and GSH kits assessed the levels of nitrogen and oxidative stress. LPS levels were detected with a Limulus Amebocyte Lysate assay. The Western blot analysis and reverse transcription-quantitative PCR detected the expression of related proteins and genes. The Elisa kit detected the level of the inflammatory factors in the cell supernatant. For the vivo NAFLD experiments, in briefly, mice were randomly chosen to receive either a High-fat diet or control diet for 12 weeks. Drug treatments started after 4 weeks of feeding. Zebrafish larvae were raised separately in fish water or 7 mM thioacetamide as the control or model group for approximately 72 h. In the therapy groups, different concentrations of PCP were added to the culture environment at the same time. Results: In zebrafish, we determined the safe concentration of PCP and found that PCP could effectively reduce the pathological damage in the liver and intestines induced by the NAFLD model. In mice, PCP could slow down weight gain, hyperlipidemia, and liver steatosis caused by a high-fat diet. More importantly, PCP could reduce the destruction of the gut-vascular barrier and the translocation of endotoxins caused by a high-fat diet. Further, we found that PCP could inhibit intestinal pyroptosis by regulating PARP-1. Pyroptosis inhibitors, such as MCC950, could effectively protect the intestinal and liver damage induced by a high-fat diet. We also found that pyroptosis mainly occurred in intestinal macrophages. PCP could effectively improve the survival rate of bone marrow-derived macrophages in a high-fat environment and inhibit pyroptosis. Conclusions: These results indicated that PCP inhibited the pyroptosis of small intestinal macrophages to protect the intestinal barrier integrity under a high-fat diet. This resulted in decreased endotoxin translocation and progression of steatohepatitis. Graphical abstract: Image 1 Highlights: The therapeutic effect of Poria cocos polysaccharides on NAFLD was demonstrated from the gut-liver axis. High-Fat Diet aggravates the gut vascular barrier disruption via macrophages-pyroptosis in NAFLD. Poria cocos polysaccharides inhibited NLRP3-mediated pyroptosis to ameliorate small intestine barrier injury.